2006
DOI: 10.1080/13607860600638131
|View full text |Cite
|
Sign up to set email alerts
|

Religion, spirituality and the well-being of informal caregivers: A review, critique, and research prospectus

Abstract: The purpose of this article is to review and critique the published literature examining the relationships between religion/spirituality and caregiver well-being and to provide directions for future research. A systematic search was conducted using bibliographic databases, reference sections of articles, and by contacting experts in the field. Articles were reviewed for measurement, theoretical, and design limitations. Eighty-three studies were retrieved. Research on religion/spirituality and caregiver well-be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
1
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 113 publications
2
48
1
7
Order By: Relevance
“…Based on a comprehensive review of 84 studies, Hebert et al (2006) report that three mechanisms may link religion/spirituality to caregiver well-being: Supportive social networks, coping resources (i.e., cognitive restructuring and appraisal), and positive emotions that improve relationship quality. In this study, the finding that Hispanic caregivers who reported higher levels of organized religious participation also reported lower levels of subjective burden might be explained by the fact that such participation affords them higher levels of social support, and consequently, lower levels of burden.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a comprehensive review of 84 studies, Hebert et al (2006) report that three mechanisms may link religion/spirituality to caregiver well-being: Supportive social networks, coping resources (i.e., cognitive restructuring and appraisal), and positive emotions that improve relationship quality. In this study, the finding that Hispanic caregivers who reported higher levels of organized religious participation also reported lower levels of subjective burden might be explained by the fact that such participation affords them higher levels of social support, and consequently, lower levels of burden.…”
Section: Discussionmentioning
confidence: 99%
“…Religion is conceptually defined as a discrete set of beliefs, practices, ideas, and language embraced by a community in search of sacred or transcendent meaning (Hebert, Weinstein, Martire, & Schulz, 2006;Herrera, Lee, Nanyonjo, Laufman, & Torres-Vigil, 2009). Spirituality is often conceptually framed as a belief in (or a search for) the transcendent, or that which positively affirms human life (Herrera et al, 2009).…”
Section: Religion Spirituality and Religiositymentioning
confidence: 99%
“…Likewise, religious involvement did also not interfere with the life satisfaction of the elderly caregivers of the present study. A possible hypothesis to justify such results would be that religious involvement is quite broad and multidimensional, a factor that may hinder its measurement and association with other factors 31 .…”
Section: Discussionmentioning
confidence: 99%
“…With these caveats in mind, there are, nevertheless, a multitude of studies documenting the use of religion and spiritual belief and practice as coping tools, particularly in the context of caregiving (see Herbert et al, 2006). The predominance of caregivers in the spirituality literature is due in part to the frequency and consistency with which caregivers identify religion or spirituality as critical coping resources (e.g., Choi, Tirrito, & Mills, 2008;Herbert, Qianyu, & Schulz, 2007;Kaye & Robinson, 1994;Pargament, 1998;Shaw et al, 2002;Spurlock, 2005;Stolley et al, 1999;Stuckey, 2001;Wilks & Vonk, 2008).…”
Section: Literature Reviewmentioning
confidence: 97%
“…Of particular interest have been the intersections between coping adaptivity and religious or intrinsic spiritual belief and practice (for detailed review, see Herbert, Weinstein, Martire, & Schulz, 2006). However, although spirituality and religiosity are often used interchangeably in the literature on caregiver burden and coping, they are distinct, if overlapping, constructs (Hodge, 2001).…”
Section: Literature Reviewmentioning
confidence: 99%